Social capital, regional governance and economic performance of rural areas - concept and empirical evidence from case studies in East and West Germany - Helmut Schrader (European Regional Science Association (ERSA), 2003)
During the last two decades the economic and social conditions of rural areas in Europe have become more and more varying in accordance with different development processes. In addition to ?traditional? location factors such as infrastructure, conditions of labour markets and accessibility, so-called 'soft? location factors like social capital, regional governance and the role of local actor networks have increasingly been taken into consideration in recent studies to explain observable differences in economic performance of the regions. The paper is mainly focussed on the relationships between social capital and governance at the regional level from a theoretical and empirical point of view. Complementary to the well-known concept of social capital the term ?regional governance? is used in the sense of weakly institutionalised and network-oriented modes of co-operation between regional actors to achieve common goals. The properties of the concept will be discussed in relation to other "soft" location factors of rural economic development. The approach is developed on the basis of empirical findings drawn from a number of pair-wise comparisons of differing rural areas in terms of economic performance. The results of the case study analysis are referring to selected rural areas in the eastern and western parts of Germany. The data are derived from business surveys and computerised network analysis, which have been elaborated as the German part of an EU-funded research project regarding dynamics of rural areas (DORA). After explaining the case study approach and clarifying the definition and theoretical properties of ?regional governance? an operational conception of indicators for characterising the term in relation to social capital embodied by formal (professional-related) and informal (private-related) types of local actor networks will be presented with regard to regional-economic analysis. Differing location conditions and socio-economic contexts are taken into account. Furthermore, expert interviews with local/regional actors as well as findings derived from postal business surveys serve as information bases for the investigation. From the comparison of the two regions and their path-depending contextual properties the following conclusion can be derived: existing regional differences regarding the quality of regional governance in combination with the accumulated stock of social capital can contribute considerably to the explanation of differing development paths under similar context conditions. Therefore, the structural elements of governance at the regional and local levels of decision making should be more strongly taken into account for impact assessment of rural development policy.
Keywords: 330